INHIBITION EFFECTS OF SCORPION VENOM EXTRACTS (BUTHUS MATENSII KARSCH) ON THE GROWTH OF HUMAN BREAST CANCER MCF-7 CELLS - Li, Weiling; Li, Ye; Zhao, Yuwan; Yuan, Jieli; Mao, Weifeng (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: To observe the inhibition effects of the Buthus matensii Karsch (BmK) scorpion venom extracts on the growth of human breast cancer MCF-7 cells, and to explore its mechanisms. Methods: Two common tumor cells (SMMC7721, MCF-7) were examined for the one which wasmore sensitivity to scorpion venom by MTT method. Cell cycle was determined by flow cytometry. Immunocytochemistry was applied to detect apoptosis-related protein Caspase-3 and Bcl-2 levels, while the expression of cell cycle-related protein Cyclin D1 was shown by Western blotting. Results: Our data indicated that MCF-7 was the more sensitive cell line to scorpion venom. The extracts of scorpion venom could inhibit the growth and proliferation of MCF-7 cells. Furthermore, the extract of scorpion venom induced apoptosis through Caspase-3 up-regulation while Bcl-2 down-regulation in MCF-7 cells. In addition, the extracts of scorpion venom blocked the cells from G0/G1 phase to S phase and decreased cell cycle-related protein Cyclin D1 level after drug intervention compared with the negative control group. Conclusions: These results showed that the BmK scorpion venom extracts could inhibit the growth of MCF-7 cells by inducing apoptosis and blocking cell cycle in G0/G1 phase. The BmK scorpion venom extracts will be very valuable for the treatment of breast cancer.